The diagnostic value of rapid urine test platform UF-5000 for suspected urinary tract infection at the emergency department - Chun, Tsun Tsun Stacia; Ruan, Xiaohao; Ng, Sau Loi; Wong, Hoi Lung; Ho, Brian Sze Ho; Tsang, Chiu Fung; Lai, Terence Chun Ting; Ng, Ada Tsui Lin; Ma, Wai Kit; Lam, Wayne Pei; Na, Rong; Tsu, James Hok Leung (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: Urine culture is time consuming which may take days to get the results. Our objective is to evaluate whether the fast urinalysis and bacterial discrimination system called Sysmex UF-5000 may provide accurate microbiologic information (within minutes) compared to clinical routine test and culture in hospitalization patients for predicting urinary tract infections (UTIs). Materials and Methods: Consecutive patients who were admitted from the emergency department at Queen Mary Hospital (a tertiary hospital in Hong Kong) from June 2019 to February 2020, was enrolled in the present study. Dipstick, manual microscopic test with culture, and Sysmex UF-5000 test were performed in the urine samples at admission. Results: A total of 383 patients were finally included in the present study. UF-5000 urinalysis (area under the receiver operator characteristic curve, AUC=0.821, confidence interval, 95%CI: 0.767-0.874) outperformed dipstick test (AUC=0.602, 95%CI: 0.550-0.654, P=1.32×10-10) for predicting UTIs in patients without prior antibiotic treatment. A significant net benefit from UF-5000 was observed compared to dipstick test (NRI=39.9%, 95%CI: 19.4-60.4, P= 1.36×10-4). Urine leukocyte tested by UF-5000 had similar performance (AUC) for predicting UTI compared to manual microscopic test (P=0.27). In patients without a prior use of antibiotics, the concordance rates between UF-5000 and culture for predicting Gram positive or negative bacteriuria and a negative culture were 44.7% and 96.2%, respectively. Conclusions: UF-5000 urinalysis had significant better predictive value than dipstick urine test for predicting UTIs. It could provide fast bacterial discrimination for initiating an effective antibiotic treatment.